Liberal equality, exploitation, and the case for an unconditional basic income - White, Stuart (1997)
Comenta el libro de Philip Van Parijs "Real freedom for all : what (if anything) can justify capitalism?"
Keywords: Parijs, Philippe van; Libertad; Capitalismo; Desigualdad social; Ingreso mínimo de subsistencia